1992
DOI: 10.1021/jm00099a013
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-5-acrylic acids: potent nonpeptide angiotensin II receptor antagonists designed using a novel peptide pharmacophore model

Abstract: A series of novel nonpeptide angiotensin II receptor antagonists containing a substituted (E)-acrylic acid has been developed. The overlay of 1, an imidazole-5-acetic acid found in the patent literature, on a novel pharmacophore model of AII suggested that extension of the acid side chain and attachment of a second aryl residue to mimic the C-terminal phenylalanine region of AII would lead to increased activity. A study of extended acid side chains at C-5 of the imidazole nucleus led to the discovery of the (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…Keenan 50 et al reported synthesis of a set of substituted (E) -acrylic acid derivatives for evaluation of their activity as angiotensin II receptor. They were guided by a developed pharmacophore model which suggests that the addition of acid chain and an aryl side chain to imidazole mimicking the C-terminal phenylalanine region of native ligand would lead to increased activity.…”
Section: Acrylamides a Tool For Design Of Targetedmentioning
confidence: 99%
“…Keenan 50 et al reported synthesis of a set of substituted (E) -acrylic acid derivatives for evaluation of their activity as angiotensin II receptor. They were guided by a developed pharmacophore model which suggests that the addition of acid chain and an aryl side chain to imidazole mimicking the C-terminal phenylalanine region of native ligand would lead to increased activity.…”
Section: Acrylamides a Tool For Design Of Targetedmentioning
confidence: 99%
“…A DoM-Migita-Stille connection was established for the synthesis of 138, also undertaken for potential demonstration of angiotensin II antagonist activity (Scheme 14.28). Thus, the stannylated imidazole 134, derived by virtue of the 2-(trimethylsilyl)ethoxymethyl ether DMG, undergoes cross-coupling with the aryl triflate 135 under the standard Migita-Stille conditions to afford 136, which is further converted by conventional reactions into 138 [141]. Reversal of the tin and triflate groups of the cross-coupling partners, tested in related systems, was shown to provide higher yields.…”
Section: Dom-cross-coupling Tactics Involving Ar-ar Bond Formationmentioning
confidence: 99%
“…A more difficult but straightforward manner of investigating receptor topography consists of its covalent labeling with appropriate synthetic ligands, as previously carried out with peptidic angiotensin II-derived probes. The goal of the present study was to design the first AT 1 specific photoactivatable nonpeptide derivative. The strategy used for the development of these compounds was based on previous structure−function relationships and the prevision of appropriate synthetic schemes. We investigated a new series of molecules potentially suitable for the introduction of an azido function selected as the photoactivatable group and easy to be obtained in a tritiated form. This series was designed according to the nonpeptide AT 1 receptor antagonist SKF 108566 18,21,22 (Figure ).…”
Section: Introductionmentioning
confidence: 99%